Mycobacterial spindle cell pseudotumour: epidemiology and clinical outcomes. Issue 7 (24th January 2018) - Sfeir, Maroun M; Schuetz, Audrey; Van Besien, Koen; Borczuk, Alain C; Soave, Rosemary; Jenkins, Stephen G; Walsh, Thomas J; Small, Catherine B
Abstract : Introduction: Mycobacterial spindle cell pseudotumour (MSP) is a rare disease characterised by tumour-like local proliferation of spindle-shaped histiocytes containing acid-fast positive mycobacteria. The aim of this literature review is to describe the clinical parameters and treatment outcomes of patients with MSP. Methods: A literature search was conducted using the search terms related to mycobacteria and spindle cell tumours. A previously unreported stem cell transplant recipient from our institution diagnosed with MSP was also included. Demographics, comorbidities, site of infection, treatment and clinical outcomes were analysed. Results: Fifty-one patients were analysed. Twenty-six (51%) had HIV infection. Mycobacterium avium complex was the most frequent organism isolated in 24 (47.1%) followed by Mycobacterium tuberculosis complex in eight (16%) cases. Lymph nodes were the most common site of infection (45.1%). Twenty (39.2%) patients received antimycobacterial agents, 12 (23.5%) underwent surgical resection and six (11.8%) received antimycobacterial agents plus surgery. Treatment was successful in 24 (47.1%) patients and failed in 15 (29.4%); 13 of these 15 patients died. Antimycobacterial therapy was significantly associated with successful outcome compared with surgical resection or no treatment (P<0.001). Conclusion: MSP is a rare condition associated primarily with immunodeficiencies. Antimycobacterial therapy is significantly associated with successful outcome.